Intestinal Duplication Management in Adult Patients: A Systematic Review - Putranto, Agi S.; Siregar, Sun P.; Satrio, Taufik B. (UI Scholars Hub, 2018)
Introduction. Gastrointestinal duplication is a rare congenital abnormality found in adults. This intestinal duplication may be associated with complications i.e. perforation, bleeding, obstruction and malignancy. Degeneration to malignancy is a basic consideration to treat a radical surgery, which is preventive. This systematic review aims to provide evidences to evaluate the preventive or conservative surgery in the management. Method. A systematic review conducted according to preferred reporting items for systematic review and meta–analysis protocols (PRISMA). Literature search proceeded on PubMed and ScienceDirect using keywords